The Use of Slang Word in the Movie â€œF9: The Fast Sagaâ€ - Limeranto, Jeane Theresia; Ena, Ouda Teda (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2022)
Slang is a casual spoken language that always is used in daily conversation. It is used to build a close relationship with friends, familyr, or peers. People tend to use slang language because slang is shortened words to help people access information easier and faster. Therefore, this present study is urgent to investigate the use of slang words in the movie entitled F9: The Fast Saga (2021). This movie was released in 2021 that is worth investigating the new slang words used in this current year. The data of the study was obtained by analysing F9 The Fast Saga Movie script. The teachnique of obtaining data was non-participatory video research which help the researcher to be more objective in the research. The result of this study was analysed and categorized into several types of slang language based on Allan and Burridge (2006)'s theory. The result of this study revealed that there were four types of slang used in the movie "F9: The Fast Saga". Those four types were flippant, imitative, clipping, and fresh and creative. These types of slang have specific functions and meaning to express ideas, thought, expression, and opiniton. In addition, this current study is expected to contribute to the literature on the use of slang language. Also, it might contribute to improving and enrinching EFL learners' vocabulary knowledge and their morphological awareness of skills.